Co-optation of diversity in nationalist advertising: a case study of an Australian advertisement. Issue 5 (3rd September 2018) - Drew, Christopher; Gottschall, Kristina
ABSTRACT: Co-optation theory, more commonly used in sociology and marketing literature, has value in media and cultural studies for examination of how countercultural ideals such as diversity can be assimilated into dominant discourse, in ways that neutralize the concepts' countercultural significations. This paper demonstrates the value of co-optation theory through a case study of an Australian nationalist advertisement, which co-opts the concept of diversity and utilizes it in a way that is palatable to the imagined White Australian audience. In the process, it is argued, the concept of diversity is neutralized and stripped of its countercultural significations, and masculine Anglo-Australian identity is sustained as an idealized norm. A Foucauldian discourse analysis of the advertisement and its surrounding media reception is conducted to explore the advertisement as an instance of co-optation that was largely met uncritically, and resultantly, passed as a national adulation of an assimilationist ideal dressed as diversity.